1989
DOI: 10.1111/j.1365-2230.1989.tb00914.x
|View full text |Cite
|
Sign up to set email alerts
|

Bullous lichen planus and lichen planus pemphigoides-clinico-pathological comparisons

Abstract: Two patients with lichen planus pemphigoides and two with bullous lichen planus were compared. Lichen planus pemphigoides was clinically distinguished by a more generalized lichen planus, more extensive blistering, the need for systemic corticosteroids and by a longer course. The blister of bullous lichen planus was a subepidermal bulla showing degeneration of the epidermal basal layer and other features of lichen planus, whereas in lichen planus pemphigoides the bulla was similar to that of bullous pemphigoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 10 publications
4
42
0
Order By: Relevance
“…20,21 Thickening of basement membrane zone was observed in systemic lupus erythematosus specimen which was concurrent to findings of Alahlafi AM et al 22 HPE of follicular lichen planus showed characteristic follicular plugging, similar findings were noticed by Wilk M et al 23 in fully developed lesions of follicular lichen planus. Subepidermal bulla noticed in the bullous lichen planus was a typical feature as reported by authours 24,25 in earlier reports and studies. Lichen sclerosus et atrophicus characteristic feature of follicular plugging was seen in both the specimen which has also been noticed by Kowalewski et al 26 Parakeratosis was seen in oral lichen planus specimen.…”
Section: Featuressupporting
confidence: 63%
“…20,21 Thickening of basement membrane zone was observed in systemic lupus erythematosus specimen which was concurrent to findings of Alahlafi AM et al 22 HPE of follicular lichen planus showed characteristic follicular plugging, similar findings were noticed by Wilk M et al 23 in fully developed lesions of follicular lichen planus. Subepidermal bulla noticed in the bullous lichen planus was a typical feature as reported by authours 24,25 in earlier reports and studies. Lichen sclerosus et atrophicus characteristic feature of follicular plugging was seen in both the specimen which has also been noticed by Kowalewski et al 26 Parakeratosis was seen in oral lichen planus specimen.…”
Section: Featuressupporting
confidence: 63%
“…According to a recent clinical description, BLP blisters develop 'on long-standing LP lesions' [12] or 'on erythem atous skin, or normal-appearing skin' [13]. DIF findings are those of LP, and in no way do they remind of bullous pem phigoid [9], IIF performed on an autologous or allogenic LP papular substrate has been said to show immunoglobu lin deposits in the granular layer as in classical LP. In fact, this is true only in 50% of cases 113.…”
Section: Discussionmentioning
confidence: 99%
“…They have been described either as LP pemphigoid (LPP) or bullous LP (BLP) [9], In LPP. the eruption is acute and consists in large bullae on both involved and uninvolved skin.…”
Section: Discussionmentioning
confidence: 99%
“…22 Direct immunofluoresence shows linear deposition of IgG and C3 along the dermoepidermal junction. 23,24 Immuno-electron microscopic studies show this deposition to be localized at the base of the bulla, in contrast to BLP where it appears to be on its roof. 25 As in bullous pemphigoid (BP), there are circulating IgG autoantibodies against 180kDa BP antigen and specifically against its major extracellular non-collagenic part.…”
Section: Differential Diagnosismentioning
confidence: 99%